Voice disorders in teachers. Implications for occupational health nursing care - Marta Regina Cezar Vaz; Luana de Oliveira Severo; Anelise Miritz Borges; Clarice Alves Bonow; Laurelize Pereira Rocha; Marlise Capa Verde de Almeida (Universidad de Antioquia, 2013)
Objective. To identify the occupational characteristics and their implications for the occurrence of voice disorders among teachers in early childhood and primary education. Methodology. A quantitative and exploratory research was undertaken in a metropolitan city of the state capital of Rio Grande do Sul/Brazil. The sample consisted of 37 teachers from early childhood and primary education. Results. All participants were female, with a mean age of 40 years. Seventy-eight percent indicated one or more voice disorders (54% hoarseness, 41% voice cracks, 27% voice loss and 3% coughing). The noisy school environment was identified as a possible triggering factor of the voice disorder in 49% of cases. Forty-six percent of all teachers indicated not doing any treatment in case of voice disorders. The most frequently used specific measures were: medication use (32%) and speech therapy (5%). Conclusion. Voice disorders are frequent among the participating teachers and are mainly related to a noisy school environment. It is important for the nurse to intervene, using educative strategies to reduce the risk factors for the vocal health of teachers working in these conditions.